Pelatihan Geogebra bagi Guru di Kota Balikpapan - Sigit Pancahayani; Syalam Ali Wira Dinata Simatupang; Abrari Noor Hasmi; Winarni (Universitas Lancang Kuning, 2022)
Mathematics is frequently thought as a hard course by students because of some reasons. One of the reasons is that students cannot visualize the material given by their teacher. On the other hand, only a few numbers of teachers who can explain the course using appropriate figures. Moreover, during a presentation or making a quiz, they cannot present those things very well which confused the students further. Facing this challenge, therefore, we organized a training to enhance the Mathematics teachers’ competency in Balikpapan City so they could attract students’ attention and improve comprehension by giving the right visualization. In this training, we used GeoGebra, which is an open-source program and user-friendly. For the result, this training performed that the participants then could graph some functions, construct a 3-D space, and make a presentation using GeoGebra.